Enhancing District Police Cyber Cell Responses to Cyber Fraud: Challenges, Strategies, and Best Practices - Singh, Dharmendra (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
Cyber fraud has emerged as a significant challenge in India’s rapidly digitizing economy, necessitating robust mechanisms for prevention, detection, and resolution. This study examines the role of digital portals, public awareness programs, and dedicated cyber police stations in enhancing district-level responses to cyber fraud, with Bhilwara District, Rajasthan, serving as a case study. By leveraging data from portals such as Pratibimb, CEIR, JMIS, and NCRP, along with outcomes from local interventions, the research highlights key trends in complaint registration, financial recovery, and public engagement. Findings reveal a substantial increase in cybercrime reporting and the effectiveness of specialized tools in blocking stolen assets, freezing fraudulent accounts, and facilitating inter-state coordination. Public awareness programs have significantly contributed to these outcomes by fostering greater public participation and understanding of cybercrime reporting mechanisms. However, challenges such as resource constraints, declining recovery percentages, and regional disparities in complaint volumes persist. This paper identifies best practices, including the strategic deployment of digital tools and focused awareness campaigns, and proposes recommendations to optimize district-level responses. The study concludes by highlighting the need for enhanced resource allocation, advanced technological integration, and expanded public-private collaboration to address the evolving threat of cyber fraud effectively.